The science of environmental pollution - Spellman, Frank R. (CRC Press, 2021)
"This new edition of The Science of Environmental Pollution presents common-sense approaches and practical examples based on scientific principles, models, and observations, but keeps the text lively and understandable for scientists and non-scientists alike. It addresses the important questions regarding environmental pollution: What is it? What is its impact? What are the causes and how can we mitigate them? But more than this, it stimulates new ways to think about the issues and their possible solutions. This fourth edition has been updated throughout, and greatly expands its coverage of endocrine disruptors and includes all new information on persistent "forever chemicals." Environmental issues continue to attract attention at all levels. Some sources say that pollution is the direct cause of climate change; others deny that the possibility even exists. This text sorts through the hyperbole, providing concepts and guidelines that not only aid in understanding the issues, but equip readers with the scientific rationale required to make informed decisions. Features: Updated throughout, and contains a new chapter on the effects of endocrine disruptors in the environment. Provides an introduction to air, soil, and water pollution sources and remediation. Addresses pressing issues such as global climate change, rising sea levels, polluted air, increased weather phenomena, and the state of potable water worldwide. Supplies a vital information source for policy-makers involved in decisions concerning environmental management. Includes case studies, examples, and study questions. The Science of Environmental Pollution is suitable for students taking undergraduate-level courses dealing with the environment and related pollution issues. It will also serve as a useful reference for environmental managers, politicians, legal experts, and interested general readers"--